Complementary structure for designer localized surface plasmons - Gao, Zhen (2016)
Magnetic localized surface plasmons (LSPs) supported on metallic structures corrugated by very long and curved grooves have been recently proposed and demonstrated on an extremely thin metallic spiral structure (MSS) in the microwave regime. However, the mode profile for the magnetic LSPs was demonstrated by measuring only the electric field, not the magnetic field. Here, based on Babinet's principle, we propose a Babinet-inverted, or complementary MSS whose electric/magnetic mode profiles match the magnetic/electric mode profiles of MSS. This complementarity of mode profiles allows mapping the magnetic field distribution of magnetic LSP mode profile on MSS by measuring the electric field distribution of the corresponding mode on complementary MSS. Experiment at microwave frequencies also demonstrate the use of complementary MSS in sensing refractive-index change in the environment.